Evidence Brief: Taking a Step Towards Achieving Worry-free Surgery in Ontario - Gauvin, François-Pierre; Wilson, MG; Lavis, JN (My University, 2017)
An assessment of what is known about problems related to worry-free surgery, options for addressing these problems, and key implementation considerations. The evidence brief was an input to a stakeholder dialogue on the topic of taking a step towards achieving worry-free surgery in Ontario.
Keywords: worry-free; surgery